Preparation of flat sheet cellulose acetate dialysis membrane, suitable for clearance of urea solution - Idris, Ani; Lee, K. Y. (Universiti Teknologi Petronas, 2004)
Flat sheet cellulose acetate dialysis membranes were prepared using phase inversion method using acetic acid as the solvent. Effect of modifying agent (polyethylene glycol 400 - PEG 400) and non solvent (distillated water) were investigated. Six different formulations were used, and the performances of the obtained membranes were tested for protein separation using a 1 mg/mL urea solution. It was found that the membrane obtained from the formulation consisting of 20% wt cellulose acetate, 60% wt acetic acid, 15 %wt PEG 400 and 5% wt distillated water gives the best c1earance performance for urea solutions. In addition, it was found that the presence of modifying agents in the casting solutions enhanced the clearance performance. Different amount of different modifying agents presence in the casting solutions will gives a totally different trend of results achieved. However, the amount of modifying agents is restricted in the range of 20% wt to avoid weakness in solutes clearance efficiency.